Pengaruh Motivasi Siswa dan Keterampilan Berpikir Kritis Terhadap Prestasi Belajar Pada Mata Pelajaran Sosiologi Di SMA Negeri 12 Garut - Lediawati, Teni Siti; Turhan Yani, Muhammad; Sarmini, Sarmini (Perkumpulan Manajer Pendidikan Islam Indonesia (PERMAPENDIS) Prov. Sumatera Utara, 2025)
This research focuses on investigating the joint influence of critical thinking skills and learning motivation on student performance in social studies courses. The research was conducted at one junior high school in East Jakarta using a survey approach. The sample consisted of 80 students selected through simple random sampling. Data collection was carried out by distributing questionnaires directly to participants. The data analysis procedure uses SPSS version 22, using instruments in the form of questionnaires and final exams. The findings of this research show that: (1) Critical thinking skills and learning motivation together have a big influence on social studies learning achievement; (2) Critical thinking skills have a significant independent influence on the success of social studies learning; and (3) Learning motivation also has a significant effect on academic achievement.